Beyond territoriality: Rethinking human mobility, border security and geopolitical space from the Indonesian island of Bintan. (June 2014) - McNevin, Anne
The key contention of this article is that contemporary practices of border security threaten to outrun the explanatory capacity of the spatial (territorial) and subject (citizen/migrant) registers habitually employed to think through human mobility. This represents a political problem as much as an empirical one. First, it implies that migration scholarship deploying categories of analysis informed by prevailing registers offers a limited perspective on contemporary techniques of migration governance; second, it suggests that such scholarship obscures the operation of power that works to enforce profoundly unequal hierarchies of mobility and represent them as politically neutral. In this article, I propose that resisting reversion to problematic categories of analysis offers the potential to think of human mobility without the state and territory as its foremost container concepts. I contend that such an approach – 'beyond territoriality' – is a crucial step on the way to negotiating the normative dimensions of border politics. The case is developed empirically via a grounded investigation of the mundane yet symptomatic practices of border security on the Indonesian island of Bintan.